The effect of a thiamin derivative on exercise performance - Webster, M. J.; Schett, T. P.; Doylle, M. R.; Branz, M. (European Journal of Applied Physiology, 1997)
The results of this study suggest that thiamin derivative supplementation does not influence high-intensity exercise performance.